AUDIT KOMUNIKASI PENERAPAN KONSEP SMART CITY MELALUI PROGRAM SMART GOVERNANCE DI DISKOMINFO KOTA PADANG - Elva Ronaning Roem; Sarmiati Sarmiati; Deby Fortunela Fortunela (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Smart governance is one of the dimensions of a smart city that specializes in governance. Smart governance is part of the Smart City goals related to public services, where public services are the main driver in the implementation of Smart Governance. To improve public services, Diskominfo has programs to support public services. This study aims to see how the communication audit of the Implementation of the Smart Governance Program at Diskominfo Padang City. This research is a qualitative descriptive study. The sampling technique used is purposive sampling technique. Data collection techniques using observation and interviews. The results showed that at the preparation stage, all the preparations made to formulate the program had been carefully prepared through the Smart City Master Plan, at the Implementation stage the program implementation was still not fully implemented. At the stage of implementing the Smart Governance program, Diskominfo did not socialize the program so that this program was not known to the public. Furthermore, at the Impact stage, researchers saw that this program had not been fully implemented by the Padang City Communication and Information Office.Keywords: Smart City, Smart Governance, Communication Audit